Influence of Hand-to-Hand Combat Training on Functional Fitness of Cadets at Higher Educational Establishments of the Ministry of Internal Affairs - Valeria Tyshchenko; Svitlana Karaulova; Andrii Lytvynenko; Ivan Hlukhov; Kateryna Drobot; Daryna Liuta (Kharkiv State Academy of Physical Culture, 2024)
Purpose: to analyze the influence of Hand-to-Hand Combat on functional fitness of cadets of a higher educational establishment of the national police of Ukraine. Materials and Methods. The study involved 125 Cadets at Higher Educational Establishments of the Ministry of Internal Affairs. Research methods: methods of theoretical level of research; empirical research methods: pedagogical observation, pedagogical experiment; chest rheography (to determine functional state of the cardiovascular system); assessment of anaerobic performance according to the Wingate test and physical performance according to the PWC170 test; methods of mathematical statistics. Results: the service and combat activities of police officers in modern social and political environment in Ukraine set high demands to functional capabilities of the body. Hand-to-hand combat can have a significant impact on professional and psychophysiological fitness of personnel for effective actions to apprehend and detain a criminal, as well as under conditions of limited space. Hand-to-hand combat is an effective sport for quality formation of the process of training cadets of the Ministry of Internal Affairs, as evidenced by improvement of all indicators of cadets of the experimental group, namely: heart rate variability, anaerobic and aerobic mechanisms of motor activity. Conclusions: for the first time, data on HRV, the Wingate test and physical performance of cadets of the Ministry of Internal Affairs were obtained. The changes of these indicators under the influence of Hand-to-Hand Combat classes in annual dynamics have been presented. Positive influence of Hand-to-Hand Combat classes on functional state of cadets has been established, which contributes to increase of the efficiency of their professional activities in future. At the end of the study, cadets of the experimental group had significantly better indicators of functional fitness than the cadets of the control group. The obtained results proved that the developed training program based on the application of Hand-to-Hand Combat is effective and proves expediency of its application in practice.